Manajemen Strategis Penanganan Tahanan Teroris di Lembaga Pemasyarakatan Kelas 1 Batu Nusakambangan: Strategic Management of Treatment for Terrorist Prisoners in Class 1 Correctional Institution of Batu Nusakambangan - Rachmayanthy Rachmayanthy; Okki Oktaviandi; Padmono Wibowo; Syahrial Yuska (Society, 2020)
Terrorism crimes are an extraordinary crime where treatment and method require special strategic management. Strategic management for treatment the terrorist prisoners is one of the programs of the Directorate General of Correctional Affairs, Ministry of Law and Human Rights of the Republic of Indonesia, namely the management of human resources through the efforts of deradicalization for terrorist prisoners, especially in the Super Maximum Security of Correctional Institution. This research aims to provide strategic management for treatment the terrorist prisoners and the implementation of correctional institution' deradicalization programs for terrorist prisoners. This research was qualitative descriptive research. Data collection techniques using direct observation techniques in Focus Group Discussions, as well as in-depth interviews with the Head of Class 1 Correctional Institution of Batu Nusakambangan and terrorist prisoners as research objects. The results of this research indicate that the strategic management for treatment the terrorist prisoners was not completely relevant to the Regulation of the Minister of Law and Human Rights Number 35 of 2018 and the implementation for treatment the terrorist prisoners in Class 1 Correctional Institution of Batu Nusakambangan are still very limited. There were still constraints to implementing guidelines for special prisoners of terrorist in terms of socializing regulations, human resources, and infrastructure for special treatment for terrorist prisoners.